ANSERIFORMES OF LAKE SYSTEMS OF THE SYRDARYA DELTA (ON THE EXAMPLE OF LAKE KARTMA) N.S. SIHANOVA (Experimental biology, 2022)
Currently, there is an increase in anthropogenic pressure on the biodiversity of the lake system of the Syrdarya Delta in the arid conditions of the Kazakh part of the Aral Sea region. This contributes to the development of a number of negative processes (transformation of components of the natural environment, violation of the ecological, socio-economic situation). In this regard, there is a need to study the reaction of biological resources to the anthropogenic impact observed in the region. There is a need to conduct comprehensive research aimed at studying and assessing the rate of change in species richness and diversity in the structure of the fauna and flora of the region. Avifauna is considered one of the indicators of environmental transformation, due to its sensitivity to any changes in nature. Quantitative accounting of avifauna can serve as a reliable method for analyzing sometimes subtle shades of changes in the composition of avifauna. As a result of the research conducted in the period from 2014 to 2021, on the territory of the lake system of the Syrdarya River delta (experimental ground: lake. Cartma) revealed 8 species from 6 genera of the family Anatidae (Ducks) of the order Geese. There are swans, geese, ducks (splashing, diving). The analysis of the ecological structure of the fauna of the goose-like Lake Kartma and the adjacent territory is carried out. The classification is given by habitat, nesting, and the nature of nutrition.
Keywords: Aral Sea; Syrdarya Delta lake system; Kartma Lake; avifauna; geese